Characterization of Phytochemicals in Ulva intestinalis L. and Their Action Against SARS-CoV-2 Spike Glycoprotein Receptor-Binding Domain - Kulkarni, Seema A.; Krishnan, Sabari B.B.; Chandrasekhar, Bavya; Banerjee, Kaushani; Sohn, Honglae; Madhavan, Thirumurthy (Frontiers in Chemistry, 2021)
Coronavirus disease-2019 (COVID-19) has caused a severe impact on almost all aspects of human life and economic development. Numerous studies are being conducted to find novel therapeutic strategies to overcome COVID-19 pandemic in a much effective way. UlvaintestinalisL. (Ui), a marine microalga, known for its antiviral property,was considered for this study to determine the antiviral efficacy against severe acute respiratory syndrome-associated Coronavirus-2 (SARS-CoV-2). The algal sample was dried and subjected to ethanolic extraction, followed by purification and analysis using gas chromatography-coupled mass spectrometry (GC-MS). Forty-three known compounds were identified and docked against the S1 receptor binding domain (RBD) of the spike (S) glycoprotein. The compounds that exhibited high binding affinity to the RBD of S1 protein were further analyzed for their chemical behaviour using conceptual density-functional theory (C-DFT). Finally, pharmacokinetic properties and drug-likeliness studies were carried out to test if the compounds qualified as potential leads. The results indicated that mainly phenols, polyenes, phytosteroids, and aliphatic compounds from the extract, such as 2,4-di-tert-butylphenol (2,4-DtBP), doconexent, 4,8,13-duvatriene-1,3-diol (DTD), retinoyl-β-glucuronide 6’,3’-lactone (RBGUL), and retinal, showed better binding affinity to the target. Pharmacokinetic validation narrowed the list to 2,4-DtBP, retinal and RBGUL as the possible antiviral candidates that could inhibit the viral spike protein effectively.